Penelusuran faktor pengaruh pembiayaan Murabahah - Ardiani Ika Sulistyawati; Aprih . Santoso; Rahmad . Kurniawan (University of Darussalam Gontor, 2020)
This study is to determine the determinants of demand for murabahah financing in Islamic banking companies in Indonesia. This study uses a quantitative regression analysis method with panel data. Sampling using purposive sampling method. The data used are Indonesian Banking Statistics and Islamic Banking Statistics for the period 2013-2018. The results of the study show that the variables of inflation and foreign exchange rates have a positive and significant effect on murabahah financing demand. Another finding is that the BI Rate has a negative and significant effect on murabahah financing demand. The research suggests that companies should still pay attention to every movement from the inflation rate, the rupiah exchange rate and the BI-Rate because they have a not too big effect on Murabahah Financing